Effects of Dietary L-Theanine on Growth Performance, Antioxidation, Meat Quality, and Intestinal Microflora in White Feather Broilers With Acute Oxidative Stress - Wang, Zixi; Tang, Yanfang; Long, Lina; Zhang, Huihua (Frontiers in Veterinary Science, 2022)
In order to reduce the damage caused by oxidative stress to broilers, it is particularly important to find ways to alleviate oxidative stress. As a natural plant extract, L-theanine has a variety of biological effects, including improving antioxidant capacity, promoting growth, enhancing immunity and anti-tumor etc. This trial evaluated the effects of dietary L-theanine on growth performance, antioxidation, meat quality and intestinal microflora in White Feather Broilers. A total of 108 21-day-old 817 broilers were randomly divided into 3 groups, with 6 replicates of 6 chicks and fed a corn-soybean meal basal diet (NC group). Two experimental diets were prepared, birds in treatment were added hydrocortisone 30 mg/kg to drinking water (PC group) and fed diets supplemented with 400 mg/kg L-theanine (LT group). Compared with the NC group, at 24 d of age, PC and LT groups decreased BW, ADG and ADFI and increased in F/G (both P<0.05). Differences were observed in LT group improved SOD and GSH-Px activities in serum than that the other two groups (P<0.05) and hydrocortisone added to drinking water and the birds fed with L-theanine to basal diets had a significant increased in the concentrations of MDA in broilers in serum and liver (both P<0.05). On the 42nd day, PH45min of supplementation of PC decreased (P<0.05) than the NC and LT groups and greater the cooking loss and shear force (P<0.05). Moreover, the villi height of PC group shown a lower trend in jejunum than the NC group (P<0.05). For content of ZO-1 in duodenum, the LT group tended to higher than the NC and PC groups (P<0.05). The activity of GSH-Px in LT was increased than the PC group in liver (P<0.05). The relative abundance of Firmicutes in the LT was significant higher the NC and PC groups (P<0.05). These results suggested that the effect of acute oxidative stress on growth performance and meat quality of broilers is continuous, and dietary L-theanine could improve the decline of growth performance, meat quality, enhance the intestinal mucosal barrier, antioxidant capacity and promote the composition of intestinal flora of broilers caused by acute oxidative stress.